2003
DOI: 10.1245/aso.2003.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation in 447 Complex Unresectable Liver Tumors: Lessons Learned

Abstract: Size has the highest correlation with local recurrence, but multiple tumors and pathology may also predict local recurrence risk. Large, complex lesions can be safely serially ablated, but because of morbidity and recurrence, RFA should not replace resection as the primary treatment of resectable liver tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
1
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(151 citation statements)
references
References 12 publications
4
139
1
7
Order By: Relevance
“…Although the approach of RFA was not shown to influence survival, there was a trend towards a higher rate of recurrence with percutaneous RFA (PcRFA) (15.1%) compared to open (6.7%) and laparoscopy (9%) in a study by Bleicher et al of 153 patients treated for a total of 447 liver tumours [8]. In addition, several studies had consistently reported significantly higher complication rates with PcRFA relative to operative approaches [9,10]. Despite the perceived technical simplicity with PcRFA, the cooperation of patients' respiratory effort following sedation poses difficulty in accurate probe placement [11].…”
Section: Delivery Of Rfamentioning
confidence: 99%
See 3 more Smart Citations
“…Although the approach of RFA was not shown to influence survival, there was a trend towards a higher rate of recurrence with percutaneous RFA (PcRFA) (15.1%) compared to open (6.7%) and laparoscopy (9%) in a study by Bleicher et al of 153 patients treated for a total of 447 liver tumours [8]. In addition, several studies had consistently reported significantly higher complication rates with PcRFA relative to operative approaches [9,10]. Despite the perceived technical simplicity with PcRFA, the cooperation of patients' respiratory effort following sedation poses difficulty in accurate probe placement [11].…”
Section: Delivery Of Rfamentioning
confidence: 99%
“…As early as 1996, incorporation of neoadjuvant systemic chemotherapy into treating initially unresectable CLMs has expanded curability with sequential surgical resection [36]. Most centres have, therefore, adopted an aggressive multimodal approach in treating CLMs; offering surgical resection alone or in combination with thermal ablation provided complete tumor extirpation can be achieved with sufficient functional post-operative hepatic parenchyma [9][10][11]15,17,20,23,[25][26][27]31,[35][36][37][38][39][40][41][42][43][44]. How RFA fits into the expanded unresectable criteria today is unclear.…”
Section: Overall Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Another tool in the arsenal of cancer therapy is radiofrequency (RF) ablation. RF ablation is a safe and effective technique to destroy focal cancer lesions in a variety of locations, including the liver, bone, and kidney (1)(2)(3). Clinical research is currently under way in cancers in the lung, breast, and adrenal gland as well (4)(5)(6).…”
mentioning
confidence: 99%